Digital resilience in higher education in response to COVID-19 pandemic: Student Perceptions from Asia and Australia - Eri, Rajaraman; Gudimetla, Prasad; Star, Shaun; Rowlands, Josh; Girgla, Anit; To, Loeurt; Li, Fan; Sochea, Nhem; Bindal, Umesh (Journal of University Teaching and Learning Practice, 2021)
COVID-19 has transformed higher education learning and teaching practices globally. Tertiary students, internationally face both opportunities and challenges in learning and adapting to this paradigm shift in the delivery of education. It remains unclear how students in international contexts are responding to these changes in digital learning during and post-COVID-19. This paper aims to compare student perceptions of digital competence, confidence, and resilience in present times using data from surveys of tertiary students from Australia, Cambodia, China, India, and Malaysia. There are disparities not only in the teaching and learning pedagogies amongst these countries but also in the levels of technological advancement, infrastructure support, and pace of digital innovation in the delivery of courses. These differences have put in focus students’ both digital competencies and resilience as they pursue higher education on various digital learning platforms. Resilience includes the ability to bounce back or adapt from stress (Smith et al., 2008) Digital resilience is students’ tech-savviness and preparedness to adapt to different digital environments as they pursue higher education. This paper examines the perceptions of tertiary undergraduate students from these countries in this emerging new digital learning norm-. A total of 687 tertiary students from the aforementioned countries participated in a survey to questions related to digital competence, confidence in using and/or adapting to digital innovation, and resilience. Statistically significant attributes are identified to help better understand the challenges these culturally diverse students perceive in digital learning environments. This study will reveal barriers that impact the digital transformation of undergraduate students which can be used to recommend necessary teaching and learning support frameworks to enhance their digital competence and resilience. This will help tertiary institutions better equip all stakeholders in adapting to the new normal of higher education in the future.